Psychological and pedagogical conditions for the support of gifted children on the experience of a private lyceum named after G.V. and N.G. Riumin of Ryazan - Shiltsova J. V., Arkharova L. I., Korchagina L. M. (Psychological and Pedagogical Support of Talented Children: Problems, Directions, Approaches, Conditions, 2020)
the experience of psychological and pedagogical support of gifted children, which consists mainly in the creation of certain conditions in a private educational institution is presented in the article. On the basis of a private lyceum named after G.V. and N.G. Riumin of Ryazan, created by the founder N.V. Riumin – candidate of psychological sciences and by its director L.I. Arkharova – candidate of pedagogical sciences, head of the Pedagogy and Teacher Education Department at FSBEI of HE " Ryazan State University named for S. Yesenin", the experience of cooperation of higher education and general education institutions in the formation and upbringing of gifted children has been studied. L.I. Arkharova’s psychological and pedagogical competencies and long experience enabled to create the conditions for attracting the best teachers of Ryazan. Being rather a small city, when the teachers of the FSBEI of HE " Ryazan State University named for S. Yesenin" know the best of the best by sight, teach the potential teachers a worthy education and “see” the situation from the inside, close cooperation and interaction can be observed. Entering the lyceum, children individually reveal their potential being surrounded by care, warmth, love and attention to the personality of everyone.
Keywords: индивидуальный подход; психолого-педагогическое сопровождение; условия; conditions; одаренность; поддержка; support; giftedness; psychological and pedagogical support; individual approach